2023
DOI: 10.1111/1759-7714.14907
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of immune checkpoint inhibitor therapy in patients with pulmonary sarcomatoid carcinoma in clinical practice

Abstract: Objective Studies have suggested the potential efficacy of immune checkpoint inhibitors (ICIs) for pulmonary sarcomatoid carcinoma. This multicenter observational study was conducted to evaluate the efficacy of systemic ICI therapy and chemoradiation followed by durvalumab therapy for pulmonary sarcomatoid carcinoma. Methods We analyzed the data of patients with pulmonary sarcomatoid carcinoma who received systemic ICI therapy or chemoradiation followed by durvalumab therapy between 2016 and 2022. Results In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Nonetheless, a retrospective investigation by Inomata et al. on ICI treatment of PSC revealed that SC patients with high PD-L1 expression had no link between tumor PD-L1 expression level and survival time, and even some individuals with PD-L1 TPS≥50% had early progression or death ( 8 ). These studies exhibited considerable heterogeneity in their findings, potentially attributable to the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a retrospective investigation by Inomata et al. on ICI treatment of PSC revealed that SC patients with high PD-L1 expression had no link between tumor PD-L1 expression level and survival time, and even some individuals with PD-L1 TPS≥50% had early progression or death ( 8 ). These studies exhibited considerable heterogeneity in their findings, potentially attributable to the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anti-angiogenic therapy combined with immunotherapy can synergize with tumor cells to improve efficacy ( 47 ). The median PFS of PSC who received systemic ICI therapy was 9.6 months ( 48 ). Qian et al.…”
Section: Discussionmentioning
confidence: 99%